The Form of Peripheral Interaction - A Framework for Experience Design - Edge, Darren (CHI 2014 Workshop on Peripheral Interaction: Shaping the Research and Design Space, 2014)
By analysing a set of applications drawn from diverse domains yet all facilitating interaction on the periphery of the user’s attention, this paper derives a framework of four qualities that can be used to characterize the desired experience of peripheral interaction in general.